Transforming Mathematical Problem Solving Through AI Tools: An Investigation of Photomath Integration in Problem-Based Learning - Choirunisa, Choirunisa; Susanti, Ely (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
This study aims to determine the ability of problem solving through Problem Based Learning (PBL) on the material of the Three Variable Linear Equation System (SPLTV) assisted by Photomath. This research is qualitative descriptive research. The subjects of this research were students of class X SMA Srijaya Negara Palembang. Data collection was carried out using test, interview, and observation methods. Analysis of test data was carried out by describing the subject's ability in problem solving, and for data analysis, interviews and observations were carried out by data reduction. interviews and observations were done by data reduction, data presentation and conclusion drawing. The results showed that the subject's problem-solving ability was the subject's problem-solving ability is quite good by applying Problem Based Learning on SPLTV material assisted by Photomath can develop students' problem-solving skills. This can be seen from the students can understand the problem in the problem, make a mathematical model, solve the problem using Photomath, compile the answer conclusion from the steps that have been done and recheck the answer using Photomath.